Linear and nonlinear frequency analyses for the rotating diaphragm of the coupling. Issue 12 (29th September 2022) - Lin, Baichuan; Chen, Bo; Li, Yinghui
Abstract: The linear and nonlinear frequencies of the diaphragm are analyzed in this paper. Firstly, the nonlinear vibration equation is set up based on the d'Alembert principle considering the geometric nonlinearity. Then, the Galerkin method and improved L-P method are employed to obtain the linear and nonlinear solutions of the governing equation. And the results from the finite element method (FEM) are introduced to make a comparison to verify the correctness. Finally, the effects of several parameters such as the transmitted torque and rotating speed on the linear and nonlinear frequencies of the diaphragm are discussed.